Fragrance Formation in the of Cocoa Roasted Process (Theobroma cacao) with Roaster Temperature Variation using a Vacuum Drying Oven - Monang Sihombing; Dhanang Puspita; Mayer Tinting Sirenden (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Chocolate is cacao nib processed product which is favorite commodity in the world, nevertheless, many of consumer have not known about the process. Notable stage in cacao processing is roaster process. Cacao roasting process currently uses conventional methods, which have weaknesses like energy wastage and bioactive compounds damage. Vacuum drying oven is new roasting method which uses low pressure and temperature. Through this research, the difference of aroma development between roasting process on conventional and vacuum drying oven method was investigated. Roasted cacao was extracted by water distillation, then distillate was separated by diethyl ether partition. The extract was characterized with GC-MS. The Characterization result shown that temperature 70°C contained 11 volatile compounds and temperature 80°C, 90°C and 140°C contained 7 volatile compounds. The higher roasting temperature, the more diverse of volatile compound. The best result in cacao roasting was on vacuum drying oven at 90°C, which has similar aroma with 140°C as control sample.